Heidegger and the measure of truth - McManus, Denis, 1967- (Oxford : Oxford University Press, 2013)
Denis McManus presents a novel account of Martin Heidegger's early vision of our subjectivity and the world we inhabit. He explores key elements of Heidegger's philosophy, and argues that Heidegger's central claims identify genuine demands that must be met if we are to achieve the feat of thinking determinate thoughts about the world around us.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Heidegger, Martin, -- 1889-1976.; Ontology